POTENSI OBJEK WISATA PUNCAK KAISANTI DI KELURAHAN WOLOAN DUA KECAMATAN TOMOHON BARAT KOTA TOMOHON (Potential of Kaisanti Peak Tourism Object in Woloan Dua Village, Tomohon Barat, Tomohon City) - Ramdhan Hidayatullah; Caroline B.D. Pakasi; Vicky R.B. Moniaga (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
This study aims to determine the potential of the Puncak Kaisanti tourist attraction in Woloan Dua Village, West Tomohon District. This research was conducted from April to July 2019. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with respondents consisting of 60 tourists in the Puncak Kaisanti tourist attraction in Woloan Dua Village, Tomohon Barat District, 1 person from the management and 1 person from the Woloan Dua Village Government. Secondary data were obtained from literature, journals, internet, thesis, BPS, and Woloan Dua village government office. The results of this study indicated that the potential of the Puncak Kaisanti tourism object was classified as a potential category based on four variables, namely physical condition, tourist attraction, accessibility and supporting infrastructure.Keywords: Potential, Puncak Kaisanti, Woloan Dua Village, West Tomohon District